Influences Between Online‐Exclusive, Conjoint and Offline‐Exclusive Friendship Networks: The Moderating Role of Shyness. Issue 2 (7th January 2013) - van, Maarten Herman Walter; Zalk, Nejra Van; Kerr, Margaret; Stattin, Hakan
Abstract Prior research has indicated that shy adolescents are more motivated to form friendships online than to form friendships offline. Little is known about whether having friendships found exclusively online may impact self‐esteem and forming offline friendships for these adolescents. This study therefore aimed to provide insight into the moderating role of shyness in the longitudinal interplay between friendships in online and offline contexts in early adolescence. Adolescents and their friends (193 girls, 196 boys; Mage = 13.29) were followed with three consecutive measurements with intervals of eight months. Results showed that particularly for shy adolescents, having friends exclusively online predicted increases in self‐esteem. Self‐esteem, in turn, was found to predict forming more friendships found both offline and online and forming more friendships found exclusively offline. Thus, findings supported the social compensation perspective that shy adolescents may benefit from having friends exclusively online, as these friendships may increase self‐esteem, thereby facilitating the formation of friendships found partially and completely offline. Copyright © 2013 John Wiley & Sons, Ltd.